Pengaruh Modal Intelektual Dan Kepemimpinan Kewirausahaan Sebagai Pemoderasi Pada Kinerja Dengan Keunggulan Kompetitif Sebagai Pemediasi Di Perguruan Tinggi Swasta (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2022)
This study aims to develop science, especially intellectual models (model of human, structural, relational, and technology), entrepreneurial leadership as a moderator variable based on the competitive advantage of private colleges. The study used a qualitative approach to causal relationships between variables. The questionnaire is designed to evaluate the research model with a sample of the leaders of private colleges in LLDIKTI region II. To assess the reliability and validity of all construct sizes, an analysis of conformity factors is carried out using AMOS 21 application. The results of this study is described about the proposed model fit, intellectual capital and entrepreneurial leadership with positively correlated with competitive advantage and performance. The strongest of influence of the 4 (four) elements discussed, as follows: structure, technology, relational, and human. Intellectual capital is moderated by entrepreneurial leadership variables on competitive advantage and then the private colleges performance has a positive influence. Intellectual capital mediated by competitive advantages on performance indirectly has the same result. Meanwhile, entrepreneurship leadership that moderates the relationship between intellectual capital and competitive advantage is not significant. The model’s recommendations, designed to help the leaders of private colleges make decisions, remind your changing environment and then will affect organizational performance. The limitation of this study is the questionnaire of the number and uneven spread of samples. In the future, it is expected that other researchers can add spiritual capital, which is very fundamental in shaping human behavior.